TEP versus Lichtenstein, which one to choose? A retrospective cohort study - Urkan,Murat (2019)
SUMMARY OBJECTIVES Inguinal hernioplasty techniques have been improved since the first hernioplasty. Tension-free techniques that apply synthetic mesh materials, as in the Lichtenstein approach, are the gold standard. Laparoscopic hernioplasty is the strongest alternative to Lichtenstein. The superiority of laparoscopic hernioplasty over Lichtenstein is a major topic of debate. In this study, we aimed to find a conclusion to this debate by comparing our totally extraperitoneal (TEP) experiences with Lichtenstein experiences. METHODS Patients who underwent inguinal hernioplasty at the Gulhane Training and Research Hospital from 2013 to 2018 were included in this retrospective cohort study. The sample included 96 TEP and 90 Lichtenstein patients for a total of 186 patients. The variables assessed were hospitalization duration, postoperative early visual analog scale score, chronic pain, paresthesia, recurrence, and early postoperative complications. Data were collected from patient records and via telephone questionnaire if needed. Data analysis was done by SPSS v20, using chi-square, Fisher’s exact, and Mann-Whitney U tests. RESULTS Male/female ratios were similar between the TEP and Lichtenstein groups. There was no difference in mean age between groups (p=0.1). The hospital stay was shorter (p=0.0001), and early postoperative visual analog scale score was lower in the TEP group (p=0.003). Chronic pain, paresthesia, recurrence, and early postoperative complications (hematoma, seroma, wound infection) were similar. CONCLUSIONS TEP is superior to Lichtenstein with shorter hospitalization duration and lower rates of early postoperative pain. No difference between the two techniques was found for chronic pain. We believe that laparoscopic hernioplasty approach may be the best alternative technique for inguinal hernia repair.